Analysis, design and implementation of direct torque controlled induction motor drive based on slip angle. (2nd October 2017) - Praveen Kumar, K. V.; Vinay Kumar, T.; Srinivasa Rao, S.
Abstract: The conventional direct torque control (DTC) of induction motor drive has two main problems such as higher ripple in torque, flux and variable switching frequency. These problems are mainly due to the hysteresis controllers. Appreciable reduction of torque and flux ripple can be achieved by increasing the inverter switching frequency. Most of the torque ripples reduction methods in literature are centered on this concept. The hysteresis based approach also results in variable switching frequency that depends on operating conditions at particular speed. Hence a method for increasing the switching frequency and at the same time maintaining constant switching frequency is needed. Most researches have chosen the space vector pulse width modulation based DTC (SVM-DTC) scheme. In this paper, first the torque and flux ripple in the conventional DTC method are shown and the improvement achieved by using proposed DTC method based on slip angle is presented. A new method such as slip angle control of induction motor drive based on DTC are proposed, analyzed, simulated, and tested. It is shown that this method progressively reduces torque and flux ripple.